Chemical engineering of methylammonium lead iodide/bromide perovskites: tuning of opto-electronic properties and photovoltaic performance. Issue 43 (30th September 2015) - Park, Byung-wook; Philippe, Bertrand; Jain, Sagar M.; Zhang, Xiaoliang; Edvinsson, Tomas; Rensmo, Håkan; Zietz, Burkhard; Boschloo, Gerrit
Abstract : A convenient 1-step spincoating method for the hybrid perovskite MAPb(I1− x Br x )3 (Cl) y, with PbCl2 as lead source, enables tuning of the bandgap. Abstract : Hybrid (organic–inorganic) lead trihalide perovskites have attracted much attention in recent years due to their exceptionally promising potential for application in solar cells. Here a controlled one-step method is presented where PbCl2 is combined with three equivalents methylammonium halide (MAX, with X = I and/or Br) in polar solvents to form MAPb(I1− x Br x )3 perovskite films upon annealing in air at 145 °C. The procedure allows for a linear increment of the semiconductor bandgap from 1.60 eV to 2.33 eV by increasing the Br content. A transition from a tetragonal to a cubic structure is found when the Br fraction is larger than 0.3. X-ray photoelectron spectroscopy investigations shows that the increase of Br content is accompanied by a shift of the valence band edge to lower energy. Simultaneously, the conduction band moves to higher energy, but this shift is less pronounced. Time-resolved single-photon counting experiments of the perovskite materials on mesoporous TiO2 show faster decay kinetics for Br containing perovskites, indicative of improved electron injection into TiO2 . Interestingly, kinetics of MAPbI2.7 Br0.3 Cl y on TiO2 scaffold became faster after prolonged excitation during the measurement. In solar cell devices, MAPbI2.7 Br0.3 Cl y yielded best performance, giving more than 14% power conversion efficiency when used in combination with an n-type contact consisting of fluorine-doped tinoxide glass coated with dense TiO2 and a mesoporous Al2 O3 scaffold, and a p-type contact, spiro-MeOTAD/Ag.